Generation of Tunable Ultrastrong White‐Light Emission by Activation of a Solid Supramolecule through Bromonaphthylpyridinium Polymerization. (5th October 2022) - Hu, Yu‐Yang; Dai, Xian‐Yin; Dong, Xiaoyun; Huo, Man; Liu, Yu
Abstract: Herein, we reported solid supramolecular bromonaphthylpyridinium polymers (P‐BrNp), which exhibit tunable phosphorescence emission in the amorphous state enabled by sulfobutylether‐β‐cyclodextrin (SBE‐β‐CD) and diarylethene derivatives. The monomer BrNp gave single fluorescence emission at 490 nm, while an apparent room‐temperature phosphorescence (RTP) at 550 nm emerged for P‐BrNp copolymers with various feed ratios. Through fluorescence‐phosphorescence dual emission, P‐BrNp‐0.1 displayed an ultrahigh white‐light emission quantum yield of 83.9 %. Moreover, the subsequent assembly with SBE‐β‐CD further enhanced the phosphorescent quantum yield of P‐BrNp‐0.1 from 64.1 % to 71.3 %, accompanied by the conversion of photoluminescence emission from white to yellow. Diarylethene monomers were introduced as photoswitches to realize reversible RTP emission, which can be used in switchable data encryption and multifunctional writing ink. Abstract : A solid supramolecule based on a sulfobutylether‐β‐cyclodextrin and diarylethene derivative has been developed by a bromonaphthylpyridinium polymerization strategy. The supramolecule exhibits tunable phosphorescence emission in the amorphous state and can be applied for stimuli‐responsive data encryption and anti‐counterfeiting.